Perancangan Game Edukasi Anak Usia Dini Menggunakan Unity - Sulthan, Imada; Asqia, Misna; Suhendi, Suhendi (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The advancement of digital technology offers new opportunities in early childhood education, particularly for young learners who respond best to visual, auditory, and play-based activities. However, conventional teaching methods often fail to accommodate these characteristics, leading to decreased engagement and increased boredom. This study aims to design a digital educational game that is enjoyable, interactive, and developmentally appropriate to support the learning of basic literacy skills. The research addresses three key issues: designing a game that is relevant to early childhood needs, developing it effectively, and evaluating user responses. A qualitative approach was employed through observation, interviews, and documentation. Testing was conducted by observing children’s reactions during gameplay and exploring their learning experiences. The findings show improvements in children’s abilities, as indicated by increased post-test scores, suggesting that digital educational games can strengthen interest, focus, and comprehension of literacy concepts. In conclusion, interactive digital games serve as an effective alternative learning tool for early childhood education.